The RM Pressfit Vitamys: 5-Year Swiss Experience of the First 100 Cups. Issue 4 (July 2017) - Wyatt, Michael; Weidner, Jan; Pfluger, Dominik; Beck, Martin
Background: The RM Pressfit vitamys is a titanium particle-coated monoblock cup with vitamin E stabilised highly cross-linked polyethylene. Initial fixation is achieved via press-fit with subsequent stability by bone on-growth. This is the first study to report the 5-year results of this design. Methods: We performed a prospective cohort study according to STROBE guidelines of 100 consecutive total hip replacements (THRs) in 92 patients all with ceramic heads. Demographic data, pre/postoperative visual analogue scale (VAS) for pain and satisfaction, Harris Hip Scores (HHS) and complications were recorded. Radiographic analysis of osteolysis and loosening was complemented by EBRA (Einzel-Bild-Röntgen-Analyse) evaluation of cup movement. Results: Our cohort comprised 48 women (mean age 67; SD 10.4) and 44 men (mean age 69; SD 7.8). The mean body mass index was 27 kg/m2 (SD 4.6). Surgical indications were osteoarthritis 96%, avascular necrosis 3% and fracture 1%. 82% had a direct anterior approach, 15% anterolateral and 3% trans-gluteal. 4 surgeons were involved. 1 cup was repositioned and fixed with screws within a week of index surgery. There were 2 intraoperative femoral fractures, 3 haematomata with 1 requiring drainage and 1 deep infection settling with an open washout and modular exchange. Mean VAS satisfaction increased from 3.8 (SD 2.0) to 8.8 at 6 weeks (SD 1.4) and 9.5 (SD 1.3) at 5 years. The HHS functional scores were 58.9 (SD 13.2) preoperatively and 94.6 (SD 6.6) at 5 years. Radiographic analysis showed neither progressive radiolucency nor osteolysis. Mean migration was 1.5 mm after 5 years. Conclusions: Mid-term results of the RM Pressfit vitamys cup are encouraging.